2012
DOI: 10.1111/aje.12024
|View full text |Cite
|
Sign up to set email alerts
|

Herd composition, kinship and fission–fusion social dynamics among wild giraffe

Abstract: A variety of social systems have evolved as a consequence of competition and cooperation among individuals. Giraffe (Giraffa camelopardalis sp.) societies are an anomaly because the dearth of long-term data has produced two polar perspectives: a loose amalgamation of non-bonded individuals that sometimes coalesce into a herd and a structured social system with a fission-fusion process modifying herd composition within a community. We analysed 34 years of data collected from a population of Thornicroft's giraff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
102
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(112 citation statements)
references
References 69 publications
9
102
1
Order By: Relevance
“…If social preferences are consistently maintained over time, then they are considered relationships (Whitehead et al, 2005). We compared the levels of associations between giraffes in the Bandia reserve, with those reported for captive and wild giraffes residing in fission-fusion social systems (Bercovitch and Berry, 2012). According to the recorded AIs, we classified dyads into three categories: weak relationship (AI range 0 -0.2), medium relationship (AI range 0.2 -0.4), and strong relationship (AI range 0.4 -1).…”
Section: (A + B Together) Is the Number Of Occasions A And B Are Seenmentioning
confidence: 99%
See 2 more Smart Citations
“…If social preferences are consistently maintained over time, then they are considered relationships (Whitehead et al, 2005). We compared the levels of associations between giraffes in the Bandia reserve, with those reported for captive and wild giraffes residing in fission-fusion social systems (Bercovitch and Berry, 2012). According to the recorded AIs, we classified dyads into three categories: weak relationship (AI range 0 -0.2), medium relationship (AI range 0.2 -0.4), and strong relationship (AI range 0.4 -1).…”
Section: (A + B Together) Is the Number Of Occasions A And B Are Seenmentioning
confidence: 99%
“…In small herds strong associations developed among adult females (Fennessy, 2009). Recent studies reported that female giraffes showed significant preference for, or avoidance of, other giraffes (Bercovitch and Berry, 2012). In the wild, female giraffes form a stable population of individuals that is divided into geographically distinct subgroups, despite the absence of physical barriers (Carter et al, 2013b;van der Jeugd and Prins, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…elephants, Archie et al 2006), and relatedness sometimes does not explain association strengths at all, as in big brown bats (Eptesicus fuscus) (Metheny et al 2008). In a number of social ungulate species with higher fission-fusion dynamics, including bison (Bison bison) , wild boar (Sus scrofa) (Kaminski et al 2005), red deer (Cervus elaphus) ) and giraffe (Bercovitch and Berry 2013), mothers continue to associate to some degree with their female offspring following weaning. These associations can persist when daughters reach adulthood in some species, for example mountain goats (Oreamnos americamus) (Godde et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Such associations have been reported in some bat species Kerth et al 2011), Grevy's zebra (Equus grevyi) ), chimpanzees (Langergraber et al 2009), bottlenose dolphins (Tursiops spp.) (Frère et al 2010b), eastern grey kangaroos (Macropus giganteus) ), and giraffe (Giraffa camelopalardis) (Bercovitch and Berry 2013;). The strongest associations within a higher fission-fusion social context often occur between relatives, especially among females where female-biased philopatry occurs.…”
mentioning
confidence: 99%